HYMENOLEPIASIS NANA - Palgunadi, Bagus Uda (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
Hymenolepiasis nana is a zoonosis disease caused by infection in adult stage or larvae stage of dwarf tapeworm Hymenolepis nana , that has primarily become a parasite for humans. Human is a main infection source for other human being, even though mouse and mice can also be the infection source of this disease. In its life cycle, Hymenolepis nana doesnt need any intermediate host. The infection doesnt affect on intestinal mucosa , but it may lead to the desquamasi of epithel cell and necrosis in which the parasite attached, causing enteritis in certain severe infection cases. This disease is diagnosed by finding typical type of egg inside the patients feces. Praziquantel is a drug of choice against hymenolepiasis nana. To repress and avoid the infection, we must rise the sanitary awareness in our surroundings at the individual level and for children. Medication treatment for the infected patients is also need to prevent further contamination, and eradication of hospes recervoar as its source of infection, such as mouse and other rodents animals, is recommended as well.